POST-WAR EFFORTS TO CONTROL THE SPREAD OF NUCLEAR WEAPONS: THE NPT REGIME IN HISTORICAL PERSPECTIVE - Singh, Kaur Sheila (My University, 1991)
The 1968 Nuclear Non-Proliferation Treaty, together with the International Atomic Energy Agency's safeguard system, stands at the center of international efforts to control the spread of nuclear weapons. The NPT, in particular, represents the culmination of a decade long debate on the question of non-dissemination. It seeks primarily to halt the spread of nuclear weapons to states not already possessing them, and at the same time, seeks to halt and reverse the existing arms race. Negotiated in the mid-1960's, it was largely a product of its time. More than two decades have elapsed since the NPT was open for signature, and the nuclear environment has changed profoundly.
This study investigates the evolution of the NPT regime from the immediate aftermath of World War II, to the present. It is an attempt, above all, to recapture the historical negotiating context of the NPT in order to account for its provisions, and assess its current stability in light of a new and changing environment.
Keywords: Political Science; Political Science